Analisis Pembentukan Portofolio Saham Optimal Pada Perusahaan Yang Terdaftar Di Jakarta Islamic Index (JII) Periode 2018 – 2021 - Ilma, Shofana Fatkhatul; Hidayati, Amalia Nuril (Lembaga Publikasi Ilmiah Nusantara, 2024)
Portfolio is a method used to reduce security risk through diversification. A portfolio that is in accordance with the investor's preference for the return as well as the risk he is willing to bear. The purpose of this study is to determine the stocks that can form an optimal portfolio, to determine the proportion of funds of each stock that makes up the optimal portfolio, to determine the expected rate of return and the risk of the portfolio formed based on the Single Index Model. This research is a type of descriptive quantitative research. The research population is companies that are included in the Jakarta Islamic Index (JII) for the period 2018-2021. Sampling is carried out using a porposive sampling criterion, namely by selecting companies that are consistently included in the Jakarta Islamic Index during the study period, so that a sample of 12 stocks is obtained. The results showed (1) From the 12 stock samples, there were 5 stocks that became the optimal portfolio candidates, namely: ANTM, TPIA, INCO, ADRO, and PTBA (2) The proportion of fund allocation for each stock included: ANTM at 39%, TPIA at 17%, INCO 25%, ADRO 14%, and PTBA 6% (3) From the five optimal portfolios, it is expected to get an Expected Return of 0.0259 or 2.59% per month with a risk of 0.0340 or 3. 40% per month.